Navigating Clinical Decision Support Systems in Emergency Medical Services: Balancing Professional Judgment and Technological Integration - Puaca, Goran; Nord, Tora; Andersson, Ulf; Maurin Söderholm, Hanna (Professions and professionalism, 2025)
This article illustrates how clinical decision support systems (CDSS) are integrated into clinical reasoning and affect decision-making processes in emergency medical services (EMS). CDSS aims to assist clinical reasoning with relevant patient information and medical knowledge, facilitating decision-making. As CDSS become increasingly significant in Swedish healthcare, understanding their implementation is critical, particularly as technological innovations may reshape clinical reasoning and professionals’ decision-making. The study draws on empirical data from observations and interviews with registered nurses (RNs) in a simulation project. Findings illustrate how clinical reasoning is a collective process among colleagues and how emotions and tacit knowledge are central to professional judgment. Although RNs express confidence in technical systems assisting clinical reasoning, they remain skeptical in situations requiring compromises to their judgment based on CDSS outputs. Finally, the article problematizes the effects on RNs when working with unsynchronized or insufficiently functioning technical systems.